Genomic and epidemiological monitoring of yellow fever virus transmission potential - Faria, N. R.; Kraemer, M. U. G.; Hill, S. C.; Goes de Jesus, J.; Aguiar, R. S.; Iani, F. C. M.; Xavier, J.; Quick, J.; du Plessis, L.; Dellicour, S.; Thézé, J.; Carvalho, R. D. O.; et al. (Science (American Association for the Advancement of Science), 2018)
Despite the existence of an effective vaccine for yellow fever, there are still almost 80,000 fatalities from this infection each year. Since 2016, there has been a resurgence of cases in Africa and South America—and this at a time when the vaccine is in short supply. The worry is that yellow fever will spread from the forests to the cities, because its vector, Aedes spp. mosquitoes, are globally ubiquitous. Faria et al. integrate genomic, epidemiological, and case distribution data from Brazil to estimate patterns of geographic spread, the risks of virus exposure, and the contributions of rural versus urban transmission (see the Perspective by Barrett). Currently, the yellow fever epidemic in Brazil seems to be driven by infections acquired while visiting forested areas and indicates spillover from susceptible wild primates. Science , this issue p. 894 ; see also p. 847 MinION genomic and case data on a recent yellow fever epidemic indicate that most infections occurred during visits to forest regions. The yellow fever virus (YFV) epidemic in Brazil is the largest in decades. The recent discovery of YFV in Brazilian Aedes species mosquitos highlights a need to monitor the risk of reestablishment of urban YFV transmission in the Americas. We use a suite of epidemiological, spatial, and genomic approaches to characterize YFV transmission. We show that the age and sex distribution of human cases is characteristic of sylvatic transmission. Analysis of YFV cases combined with genomes generated locally reveals an early phase of sylvatic YFV transmission and spatial expansion toward previously YFV-free areas, followed by a rise in viral spillover to humans in late 2016. Our results establish a framework for monitoring YFV transmission in real time that will contribute to a global strategy to eliminate future YFV epidemics.